2014
DOI: 10.1111/pim.12138
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase (MMP)‐2 and MMP‐9 as inflammation markers of Trichinella spiralis and Trichinella pseudospiralis infections in mice

Abstract: Trichinella spiralis and Trichinella pseudospiralis exhibit differences in the host-parasite relationship such as the inflammatory response in parasitized muscles. Several studies indicate that matrix metalloproteinases (MMPs) represent a marker of inflammation since they regulate inflammation and immunity. The aim of this study was to evaluate the serum levels of gelatinases (MMP-9 and MMP-2) in mice experimentally infected with T. spiralis or T. pseudospiralis, to elucidate the involvement of these molecules… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…However, this expression was decreased in the groups that were treated with acetazolamide which reflects decreased expression of MMP-9 and reduction in the inflammatory changes. Bruschi et al (2014) observed that MMP-9 may be considered as markers of the inflammatory response in Trichinella spp. in infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…However, this expression was decreased in the groups that were treated with acetazolamide which reflects decreased expression of MMP-9 and reduction in the inflammatory changes. Bruschi et al (2014) observed that MMP-9 may be considered as markers of the inflammatory response in Trichinella spp. in infected mice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, leukocytes secrete proteases, such as MMPs, which are a group of proteolytic enzymes whose main function is to degrade ECM protein [145][146][147]. Matrix metalloproteinases are regarded as key molecules in inflammation, and up-regulated expression of MMP members is often associated with the presence of inflammation [146].…”
Section: Extravasation In Inflammationmentioning
confidence: 99%
“…Furthermore, leukocytes secrete proteases, such as MMPs, which are a group of proteolytic enzymes whose main function is to degrade ECM protein [145][146][147]. Matrix metalloproteinases are regarded as key molecules in inflammation, and up-regulated expression of MMP members is often associated with the presence of inflammation [146]. In addition, studies have revealed that inflammatory cells can induce the expression of MMPs, which are crucial for all stages of the inflammatory process, from tissue repair and foreign body elimination to activating cytokines [148,149].…”
Section: Extravasation In Inflammationmentioning
confidence: 99%
“…Cell surface enolase also influences MMPs that can help process the inflammatory cytokines TNF-α and IL-1β to their biologically active forms [59, 60], which in turn may further enhance inflammatory responses. Both MMP-2 and MMP-9 play important roles in the inflammatory process [61]; thus, targeting enolase may be considered for limiting ECM- and MMP-mediated damages after injury.…”
Section: Nse In Neuroinflammationmentioning
confidence: 99%